Trideuteromethylation of Alkyl and Aryl Bromides by Nickel-Catalyzed Electrochemical Reductive Cross-Electrophile Coupling - Steverlynck, Joost; Sitdikov, Ruzal; Nikolaienko, Pavlo; Kale, Ajit Prabhakar; Rueping, Magnus (Synlett, 2024)
A new nickel-catalyzed electrochemical, reductive cross-coupling for the trideuteromethylation of alkyl and aryl bromides is reported in which CD3 arenesulfonate derivatives were used as effective and readily available CD3 sources. The CD3-labeled products were obtained with good yields. It was demonstrated that this methodology is scalable and can be efficiently used for various methylations, including 13CH3 and 13CD3 labeling.
Keywords: electrosynthesis; nickel catalysis; isotopic labeling; methylation; aryl halides; cross-coupling